Teknologi Budidaya Padi Sawah Tadah Hujan untuk Meningkatkan Produktivitas dan Pendapatan Petani di Pesisir Pantai Sumatera Utara (Studi kasus Kec.Tanjung Beringin Kab.Serdang Bedagai) - Parhusip, Dorkas; H, Lermansius; S, Perdinanta; Sari G, Setia; Girsang, MA; Nainggolan, P; Marpaung, Imelda S; Sri Ulina, Evawaty (Seminar Nasional Lahan Suboptimal, 2021)
Parhusip D, H Lermansius, S Perdinanta, GS Setia, Girsang MA, Nainggolan P, Marpaung IS, Ulina ES. 2021. Rainfed rice cultivation technology to increase productivity and income of farmers in coastal North Sumatra (Study case Tanjung Beringin District Serdang Bedagai Regency). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 498-507.Â  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Serdang Bedagai Regency is one of the food crop development areas in North Sumatra which has begun to optimize sub-optimal land use such as rainfed land. Rainfed lowland rice cultivation in this area faces problems with the availability of new superior varieties, quality seeds, unbalanced use of fertilizers, and high use of pesticides. The purpose of writing this paper is to provide information on the implementation of rice cultivation technology in rainfed rice fields and provide input for improving technology for rainfed rice cultivation on the coast for the community and policy makers. This paper is a scientific review of location-specific technological innovations for rice cultivation that can be applied to rainfed rice fields, including the use of new high-quality varieties, balanced fertilization, the use of organic materials with the use of rice consulting services (LKP). The implementation of site-specific technology in rainfed rice fields is absolutely necessary to increase rice productivity and farmers' income on the coast of Serdang Bedagai Regency, North Sumatra.